PENGEMBANGAN SISTEM INFORMASI MAHASISWA BERBASIS MOBILE ANDROID HYBRID MENGGUNAKAN WEBSERVICE STUDI KASUS: POLITEKNIK PGRI BANTEN, CILEGON - Khasan Asrori; Ely Nuryani; Waliadi Gunawan (Program Studi Sistem Informasi, Universitas Banten Jaya, 2020)
The development of mobile technology is currently widely used by android smartphone, especially the most widely used. The need to use this technology is very much needed as a mobile-based information service media. The information service system for students at Politeknik PGRI Banten is currently computerized by utilizing web-base technology not yet following the development of mobile technology. Therefore, the development of a hybrid android based mobile information system service was carried out with the aim of developing an existing service system into mobile smartphone-based system service. From the results of the study, the utilization of student information system techonlogy services based on hybrid android mobile and supported by pus notification in real time can help financial and academic departements in providing information related to lecture payments and information related to lecture schedules.